Inclusion of Military Aviation Personnel Training System in the Republic of Uzbekistan - Davranov Abdullah (Global Scientific Publishing, 2023)
This article talks about the establishment of a military aviation personnel training system in the Republic of Uzbekistan. The author, relying on legal information, studied and analyzed the specific aspects of the establishment of the military aviation personnel training system in the Republic of Uzbekistan on the basis of available scientific literature.
Keywords: Uzbekistan; military; personnel training; aviation